2022
DOI: 10.4103/aja202157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermophilic bacterium HB27 manganese superoxide dismutase in a rat model of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS)

Abstract: We investigated the therapeutic effects of superoxide dismutase (SOD) from thermophilic bacterium HB27 on chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and its underlying mechanisms. A Sprague–Dawley rat model of CP/CPPS was prepared and then administered saline or Thermus thermophilic (Tt)-SOD intragastrically for 4 weeks. Prostate inflammation and fibrosis were analyzed by hematoxylin and eosin staining, and Masson staining. Alanine transaminase (ALT), aspartate transaminase (AST), serum creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Studies have shown that the increased oxidative stress and oxidative damage induced by CP are not only closely associated with the course of disease but also related to abnormal semen parameters, and they may be the cause of infertility in some patients 56,57 . Treatment strategies to increase antioxidant capacity and alleviate oxidative stress might be promising options for CP/CPPS patients 58 . MDA is produced by ROS when they react with lipoprotein membranes and polyunsaturated fatty acids at the cellular and subcellular levels, so MDA measurements provide a means of assessing the extent and severity of damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the increased oxidative stress and oxidative damage induced by CP are not only closely associated with the course of disease but also related to abnormal semen parameters, and they may be the cause of infertility in some patients 56,57 . Treatment strategies to increase antioxidant capacity and alleviate oxidative stress might be promising options for CP/CPPS patients 58 . MDA is produced by ROS when they react with lipoprotein membranes and polyunsaturated fatty acids at the cellular and subcellular levels, so MDA measurements provide a means of assessing the extent and severity of damage.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Treatment strategies to increase antioxidant capacity and alleviate oxidative stress might be promising options for CP/CPPS patients. 58 MDA is produced by ROS when they react with lipoprotein membranes and polyunsaturated fatty acids at the cellular and subcellular levels, so MDA measurements provide a means of assessing the extent and severity of damage. Moreover, superoxide radicals are converted into harmless hydrogen peroxide and oxygen molecules by SOD, an enzyme catalyst.…”
Section: Blockade Of Nrf2/ho-1 Signaling Abolished the Anti-inflammat...mentioning
confidence: 99%